ANALISIS PENERAPAN MANAJEMEN WAKTU PADA PROYEK PEMBANGUNAN GEDUNG DKK DAN GEDUNG PARKIR PANDANARAN KOTA SEMARANG ( Studi Kasus : PT. Sinar Cerah Sempurna ) - Wibowo, Doni Ari; Priyatno, Bagus; Permata Suwandi, Putri Anggi (Universitas PGRI Semarang, 2020)
Implementation of project time management is very important to ensure that the projeck can be on time. Failure in the implementation time management due to various constraints one of which is the delay of work due to the fault of the implementing party that is experiencing an obstacle. So it is very necessary to analyze the constraints faced by a construction service company in appliying the time management. The method used to analyze the factors of project time management constraints is the analysis of the Saverity index, frequency index and importance index. The study was conducted by distributing questionnaires to 25 employees of PT. Sinar Cerah Sempurna on the construction of the DKK Building and Semarang City Pandanaran Parking Building. The time performance in the construction of the DKK Building and the Semarang City Pandanaran Parking Building based on the average deviation of the project time schedule showed a figure of 4.06%. Seen from table 4.38. The deviation value indicates that the figure is included in the average category. In addition, this can be seen from the results of the ranking analysis of the constraints that occur directly proportional to the project time schedule that is in progress Ranking of the 10 major obstacles to the implementation of time management are: difficulties in procurement of labor (8.64), slow mobilization of tools (8.17), lack of supervision and financial control (7.95), conflicts with other construction activities (7.83), low labor mobilization (7.83), lack of supervision of work performance and productivity (7.61), late delivery of materials (7.61), lack of communication and coordination between project implementation teams (7.50) , lack of equipment-related supervision (7.49) late payment to suppliers or subcontractors (7.44). The ranking of dominant factors that constrain the implementation of time management is seen from the main factors, namely: Labor factor with an interest index of (7.43), Factor tools with a factor of interest index of (7.25), Financial factors with a factor of interest index of (7.22),Communication factors and coordination with an interest index of (7.15), Planning factors with an interest index of (7.01), Material factors with an interest index of (6.97) and finally a supervision factor with an index of (6.84).